THE EFFECT OF ACCOUNTING PLANT ASSETS AND LEADING COMMITMENT TO GOOD CORPORATE GOVERNANCE AND EFFECT PERFORMANCE FINANCE IN PERUM PERHUTANI HOLDING : DRAFT A PROPOSAL - Retno Martanti Endah Lestari; Ida Farida (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
This paper discuss about PSAK 69 agriculture with specific focus on accounting of plant assets can effect performance finance in Perhutani holding, Indonesia. Biological asset are plants and animals undergoing biological transformations. Biological transformation consists of the process of growing, developing, producing and ready quotes that lead to changes both qualitatively and quantitatively. This raises the needs of various parties regarding the ability of the aplication of PSAK 69 in biological asset, especially on the use of present value of the model of cash inflows in the future to determine the fair value of biological asset certain categories. The results of the proposed study would hopefully assist in the development of an alternative fair value model in valuing plant assets supported by leading commitment and subsequently lead to good corporate governance specifically on the performance finance.